2016
DOI: 10.1002/2016gl068992
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale observations of large‐amplitude, parallel, electrostatic waves associated with magnetic reconnection at the magnetopause

Abstract: We report observations from the Magnetospheric Multiscale satellites of large‐amplitude, parallel, electrostatic waves associated with magnetic reconnection at the Earth's magnetopause. The observed waves have parallel electric fields (E||) with amplitudes on the order of 100 mV/m and display nonlinear characteristics that suggest a possible net E||. These waves are observed within the ion diffusion region and adjacent to (within several electron skin depths) the electron diffusion region. They are in or near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
81
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 41 publications
15
81
1
Order By: Relevance
“…In regions where hot and cold plasmas interpenetrate, electron‐acoustic wave damping is reduced and these waves evolve into nonlinear electron‐acoustic solitary structures. Other simulations of electron‐acoustic wave generation in regions where hot and cold plasma interpenetrate produce similar results (Ergun, Holmes, et al, ).…”
Section: Observationssupporting
confidence: 59%
“…In regions where hot and cold plasmas interpenetrate, electron‐acoustic wave damping is reduced and these waves evolve into nonlinear electron‐acoustic solitary structures. Other simulations of electron‐acoustic wave generation in regions where hot and cold plasma interpenetrate produce similar results (Ergun, Holmes, et al, ).…”
Section: Observationssupporting
confidence: 59%
“…Due to the long duration of the magnetopause crossing (∼30 s), it is possible that the configuration of the magnetopause changed over the course of the event. It is also possible that kinetic‐scale instabilities cause the local current and boundary orientations to differ from the larger‐scale configuration (Ergun, Holmes, et al, ; Ergun et al, ; Price et al, , ). Four‐point timing analysis (Schwartz, ) of the B Z G S E reversal point (at approximately 07:36:55 UT) yields a normal vector of [0.98011, 0.192104, −0.049797], again in GSE, and a boundary velocity of −31 km/s trueN̂.…”
Section: Data Analysis Methods and Lmn Coordinatesmentioning
confidence: 99%
“…Ergun, Holmes, et al () and Ergun et al () reported observations of large‐amplitude parallel electrostatic waves, which they associated with drift‐instability‐driven “corrugations” of the magnetopause near the separatrix and X‐point. Cassak et al () and Genestreti et al () reported trueJ·(trueE+trueve×trueB)>0, the local per‐volume rate of work done on the plasma by the nonideal electric field, in central EDRs that were several orders of magnitude larger than what was predicted by 2.5‐d particle‐in‐cell (PIC) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This modification of the Hall physics due to cold ions has been studied through investigating the generalized Ohm's law using observations from the Cluster (Toledo‐Redondo et al, ) and Magnetospheric Multiscale (André et al, ) spacecraft. Lower hybrid waves (Graham et al, ), ion acoustic waves (Uchino et al, ), and electron acoustic waves (Ergun, Holmes, et al, ) can be generated at the magnetopause boundary layer due to the interaction of magnetosheath and cold magnetospheric plasmas. Thus, cold ions can affect the magnetic reconnection in both the fluid and kinetic aspects.…”
Section: Introductionmentioning
confidence: 99%